A rare presentation of ruptured amoebic liver abscess with caecal perforation - a case series - Kopperundevi, V.; G., Vimala; Vyshnavi Y., Sai; R., Kannan (International Surgery Journal, 2022)
A rare complication of simultaneous rupture of liver abscess with caecal perforation occurs mainly in malnourished patients and carries a high mortality rate. In invasive amoebiasis, the trophozoites penetrate the intestinal mucosal layer causing amoebic colitis which is carried along the portal circulation to produce liver abscess that is more prone to rupture in cases of immunocompromised status. Here we report 4 cases of ruptured liver abscess associated with caecal gangrene which were operated at our institute. All 4 patients were male who were chronic alcoholics and presented with ruptured amoebic liver abscess and simultaneous perforation of caecum that was identified on exploratory laparotomy. The different approaches to surgical management of these patients is discussed, wherein early identification and timely intervention remain as mainstay of treatment in all cases.